2020
DOI: 10.1242/dev.193813
|View full text |Cite
|
Sign up to set email alerts
|

Axial skeleton anterior-posterior patterning is regulated through feedback regulation between Meis transcription factors and retinoic acid

Abstract: Vertebrate axial skeletal patterning is controlled by co-linear expression of Hox genes and axial level-dependent activity of HOX protein combinations. MEIS transcription factors act as co-factors of HOX proteins and profusely bind to Hox complex DNA; however, their roles in mammalian axial patterning remain unknown. Retinoic acid (RA) is known to regulate axial skeletal element identity through the transcriptional activity of its receptors; however, whether this role is related to MEIS/HOX activity remains un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 79 publications
1
5
0
1
Order By: Relevance
“…The first COVET DC reveals that scRNA-seq cells are correctly enriched for Hoxd4 48,52 (anterior) and Hoxb9 53 (posterior) markers in their respective domains, consistent with seqFISH expression in NMP and spine cells (Fig. 5c).…”
Section: Envi Learns Spatial Gradients From Single-cell Datasupporting
confidence: 71%
See 1 more Smart Citation
“…The first COVET DC reveals that scRNA-seq cells are correctly enriched for Hoxd4 48,52 (anterior) and Hoxb9 53 (posterior) markers in their respective domains, consistent with seqFISH expression in NMP and spine cells (Fig. 5c).…”
Section: Envi Learns Spatial Gradients From Single-cell Datasupporting
confidence: 71%
“…Hoxb7 and Tlx2 78 ) and anterior genes (Foxa3 79,80 , Hoxd3 52 , Hoxa2 [81][82][83] , Rfx4 and Hoxd4).…”
Section: Mapping Cortical Depth Of Dissociated Neurons With Merfishunclassified
“…Indeed, putative enhancer regions identified in pSHF cells revealed enrichment for HOX and TALE binding motifs (Stefanovic et al, 2020). While HOX and MEIS genes appear to be direct targets of RA itself (Mercader et al, 2000;Berenguer et al, 2020), studies have shown that they can also regulate Raldh2 expression and thereby RA levels through a positive feedback loop (Vitobello et al, 2011;Lo ´pez-Delgado et al, 2021). Interestingly, misexpression of Hoxb1 in the aSHF domain resulted in an upregulation of Tbx5 and Nr2f2 (Stefanovic et al, 2020), both of which are implicated in the differentiation of atrial and sinoatrial nodal cells in vivo and in vitro (Liberatore et al, 2000;Wu et al, 2013;Devalla et al, 2015;Protze et al, 2017).…”
Section: Stem Cell Reportsmentioning
confidence: 99%
“…During embryo development, Meis1 ablation results in hematopoietic, vascular, and ocular defects [2,3]. It has been also well defined the role of Meis1 and Meis2 in mouse axial skeleton formation [7][8][9] and in anterior-posterior patterning for limb initiation [10], for which Meis loss-of-function (Meis1 and Meis2 double knock-out) embryos are limbless, with undeveloped appendicular condensations.…”
Section: Introductionmentioning
confidence: 99%